Do male couples agree on their sexual agreements? An analysis of dyadic data - Sharma, Akshay (Arch Sex Behav, 2019)
Male couples often formulate sexual agreements, but little is known about the extent to which partners concur about their exact terms. Disagreements, particularly with respect to sex outside the relationship, may induce stress and potentially increase the risk of HIV and other sexually transmitted infections. Our study sought to describe concordance between male partners on several aspects of their sexual agreements, overall, as well as stratified by dyadic HIV serostatus and relationship duration. Between July 2014 and May 2016, we collected bidirectional data from 160 male couples residing in Atlanta, Boston, and Chicago. Overall, we observed weak concordance for whether or not couples had a mutual agreement about sex with outside partners. Even among 110 couples in which both partners reported having an agreement, there was weak to moderate concordance for general rules that might apply to having sex outside the relationship (e.g., forming emotional relationships is not allowed, outside sexual activities must be disclosed), and for specific sexual behaviors allowed or disallowed (e.g., topping without a condom, bottoming without a condom). Concordance for the type of sexual agreement was higher within HIV seroconcordant negative partnerships compared to HIV serodiscordant partnerships, and lower within relationships ≥5 years and 1 to <5 years compared to those <1 year. Dyadic interventions for male couples (e.g. couples HIV testing and counseling, relationship education programs) can offer unique opportunities for skills building around negotiating sexual agreements, and might especially benefit HIV serodiscordant partnerships, and those in the formative stages of their relationships.